Preparation and Evaluation of the Cytoprotective Activity of Micelles with DSPE-PEG-C60 as a Carrier Against Doxorubicin-Induced Cytotoxicity - Xu, Beihua; Ding, Zhongpeng; Hu, Ying; Zhang, Ting; Shi, Senlin; Yu, Guangmao; Qi, Xuchen (Frontiers in Pharmacology, 2022)
To deliver doxorubicin (DOX) with enhanced efficacy and safety in vivo, fullerenol-modified micelles were prepared with the amphiphilic polymer DSPE-PEG-C60 as a carrier, which was synthesized by linking C60(OH)22 with DSPE-PEG-NH2. Studies of its particle size, PDI, zeta potential and encapsulation efficiency were performed. DOX was successfully loaded into the micelles, exhibiting a suitable particle size (97 nm, 211 nm, 260 nm, vector: DOX =5:1,  10:1; 15:1 (W/W)), a negative zeta potential of around −30 mv, and an acceptable encapsulation efficiency (86.1%, 95.4%, 97.5%, vector: DOX =5:1, 10:1; 15:1 (W/W)). The release behaviors of DOX from DSPE-PEG-C60 micelles was consistent with the DSPE-PEG micelles and it showed sustained release. There was lower cytotoxicity of DSPE-PEG-C60 micelles on normal cell lines (L02, H9c2, GES-1) compared with free DOX and DSPE-PEG micelles. We explored the protective role of DSPE-PEG-C60 on doxorubicin-induced cardiomyocyte damage in H9c2 cells, which were evaluated with a Reactive Oxygen Species (ROS) Assay Kit, JC-1, and a FITC Annexin V Apoptosis Detection Kit for cellular oxidative stress, mitochondrial membrane potential, and apoptosis. The results showed that H9c2 cells exposed to DSPE-PEG-C60 micelles displayed decreased intracellular ROS, an increased ratio of red fluorescence (JC-1 aggregates) to green fluorescence (JC-1 monomers), and a lower apoptotic ratio than the control and DSPE-PEG micelle cells. In conclusion, the prepared DOX-loaded DSPE-PEG-C60 micelles have great promise for safe, effective tumor therapy.